A Study on Attitutes of Postgraduate Students In Educational Sciences And Teaching Departments Towards Distance Education In Terms of Various Variables - BALABAN DAĞAL, ASUDE; RAMAZAN, MÜSLİMAT OYA (My University, 2024)
The aim of this study is to investigate the attitudes of postgraduate students in the fields of educational science and teaching at universities in Turkiye towards distance learning, in terms of different variables, in the spring semester of the 2019-2020 academic year. Mixed method sequential explanatory design was used in the study. The sample of the study was determined using the snowball sampling method. The sample consisted of a total of 321 students, of which 238 were female (74.1%) and 83 were male (24.9%). The data of the study were collected through the Personal Information Form and the Attitude Towards Distance Education Scale. As a result of the analysis of the data obtained from the scale, it was found that the students' attitude towards distance education was undecided. As a result of the analysis, a significant difference at .05 level was found in favour of doctoral students according to the variable of postgraduate degree. A significant difference at the .05 level was found in favour of distance learning students according to whether they took distance learning before the pandemic, and in favour of distance learning students according to whether they took distance learning during the pandemic. The results of the research are important in terms of revealing the attitudes and opinions of students exposed to distance education with a rapid transition during the pandemic process. Keywords: Distance learning, post graduate education, educational sciences, attitude
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Social Sciences and Humanities; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Distance learning; post graduate education; educational sciences; attitude